Whole body computed tomography with interactive cros-sectional anatomy - Wegener, Otto H. (Verlag : Blackwell Science, 1995)
(Producer) Contains the entire 2nd rev. ed. of the standard work on CT diagnosis, with additional multimedia functions that have expanded the book and provided a new means of access to its contents. Contains over 1500 individual images and interactive cross-sectional anatomy
CD is available at Koleksi Media Perpustakaan HUKM
System requirements: IBM-compatible PC with an 80386 processor (80486, 33 MHz or higher recommended); 4 MB RAM (8MB recommended), at least 5 MB free hard disk space; MS-DOS 5.0 or higher; Microsift Windows 3.1 or higher; SVGA graphics card (800 x 600, 256 colors); double-speed CD-ROM drive
Keywords: Tomography, X-Ray Computed; Anatomy, Regional